Saving 20, 000 Days and Beyond using breakthrough improvements: lessons from an adaption of the Breakthrough Series Collaborative. Issue 2 (April 2020) - Middleton, Lesley; Gray, Jonathon; Dowdle, Diana; Villa, Luis; Cumming, Jacqueline; O'Loughlin, Claire
Objectives: To report on selected findings from an evaluation of two consecutive quality improvement campaigns that adapted the Breakthrough Series Collaborative model to the broad topic of reducing demand for hospital care and reflect on lessons learned from their adaption of the model for subsequent collaborative improvement efforts. Methods: We conducted a series of semi-structured interviews with Campaign sponsors and Collaborative team leaders as part of the broader realist evaluation of the two Campaigns. In addition, follow-up semi-structured interviews with Campaign sponsors and implementers were undertaken three years after the evaluation concluded (ex post evaluation interviews) to understand which adaptions to the Breakthrough Series Collaborative model had been the most influential. Results: The interviews explored two features that differentiated the Campaigns from other Breakthrough Series Collaboratives. Firstly, the Campaigns enabled a diverse range of improvement solutions to be tested which had implications for the collaborative nature of the learning collaboratives. Secondly, two sequential Campaigns were implemented that incorporated common elements and provided the opportunity for the transfer of knowledge from one Campaign to the next. Conclusions: Given widespread pressure to transform health care into a learning system, this paper provides a practical example of using cumulative insights to encourage the sustainability of collaborative improvement efforts. These insights centre on the gains from spreading improvement methodology throughout the organization and learning how to select and support successful collaborative teams.